O fundamento do direito político em Rousseau: antropologia - Cá, Lili Pontinta (Universidade Federal de São Carlos, 2021)
The present research aims to examine the principle of legitimacy of the political right in Jean-Jacques Rousseau. The life in society through legitimate rules originary of exercise of the general will sovereign. However, the general will although sovereign and right not would confer legitimacy in whatever circumstance. Seem us that Rousseau find in the anthropology the principle of legitimacy of the rules of the sociability instituted by men, namely, the freedom, pity and equality. Then it is intented to investigate if and to what extent Rousseau invokes the anthropology to think the legitimacy of the rules of coexistence in the society.
The foundation of political right in Rousseau: anthropology
Keywords: Antropologia; Legitimidade; Direito natural; Direito político; Anthropology; Legitimate; Natural right; Political right; CIENCIAS HUMANAS::FILOSOFIA::HISTORIA DA FILOSOFIA